Disrupters : success strategies from women who break the mold - Fletcher, Patti (Gildan Audio, 2019)
Disrupters shows what different women in business have done to reach success as they define it. From board members to CEOs to freelancers, the business world is stacked against women because they follow the unspoken rules of business culture made long before women entered the workforce. Tech executive, board member, and angel investor Dr. Patti Fletcher recognizes those rules and then showcases the women who have found success by breaking them. With exciting insights and uplifting stories, Disrupters demystifies what it takes to go where so few have gone before by: - Exploring the mindsets that help or hinder success against all odds - Discovering the right time to begin the journey to a role that feels too big and too hard to obtain - Learning the habits, tactics, and relationships that separate those who succeed from those who do not - Building a personal board of directors that will catapult you to the professional boardroom - Revealing what it means to achieve your own version of success with case studies and interviews with women of diverse races, ages, backgrounds, and industries.